WELLHEAD: a Collaborative Approach to Spiritual Assessment and Intervention, Developed with People with Aphasia - Mumby, Katharyn Joanna; Grace, David (Health and Social Care Chaplaincy, 2020)
Spirituality is a neglected aspect of healthcare and rehabilitation for those with acquired communication difficulties such as aphasia (language impairment) as a consequence of stroke, neurological disease and dementia. Collaborative working between health professionals and chaplaincy services in promoting spiritual health is desirable and necessary in the context of barriers to the delivery of spiritual care, which are explored from a hospital speech and language therapy perspective. Terminological and institutional barriers, restricted care provision, lack of knowledge and awareness, and lack of resources appropriate in communication impairment, gave rise to “WELLHEAD”, a novel approach to spiritual health assessment, intervention and outcomes measurement originated by Dr Katharyn Mumby. The article describes the theoretical framework and content of WELLHEAD. Reflections are outlined about the positive collaboration between speech and language therapy, chaplaincy services and people with aphasia in feasibility work with WELLHEAD, an approach offering tools for further application and development.